Comparison of Prognostic Scores for Upper Gastrointestinal Bleeding in the Hepato-Gastro-Enterology Department - Saeed Ur Rehman, Azhar Saeed, Adnan Ghafoor, Shafqat Ur Rehman Orakzai, Ajmaal Jami, Amanullah Khokhar (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The goal of this study is to assess the relative value of individual UGIB prognostic scores in predicting patient outcomes. Patients and Methods: This study was a descriptive cross-sectional analysis of data collected before. Included were patients admitted to the Al Tibri Medical college and hospital Malir Karachi Center and Fauji foundation Rawalpindi with upper GI bleeding and treated in the Gastroenterology Division. Analyses in this study compared the predictive power of five different prognostic scores (the Glasgow Coma Scale, modified Glasgow Coma Scale, coagulation risk score, and acute ischemic stroke severity score; together, these scores are known as GBS, mGBS, FRS, CRS, and AIMS65) for the occurrence of death and rebleeding within 42 days. ROC (Receiver Operating Characteristic) curves were used to compare the various scores. Results: A total of 314 individuals were enrolled in the study, with a male-to-female sex ratio of 2.48. In 70.94% of cases, fibroscopy revealed UGIB due to portal hypertension unrelated to peptic ulcer disease. The "FRS" score was the most reliable predictor of mortality or rebleeding for all patients. Compared to other scores, the "FRS" provided the best reliable forecast of whether or not patients would have spots. The "FRS" score was the most reliable one for predicting mortality. Patients deemed to be at low risk (below the threshold value) had a mortality rate of 2.2% according to the "FRS," 9.3% according to the "CRS," 0% according to the "GBS" (p = 0.565), 50% according to the "mGBS," and 11.42% according to the "AIMS65." The predictive value of UGIB scores was higher for incidental portal hypertension. Conclusion: Upper gastrointestinal hemorrhage cases can be accurately predicted using the "FRS" and "CRS" scores. But in the setting of portal hypertension, these scores did badly. UGIB Keywords: Prognostic Scores, Upper Gastrointestinal Bleeding, Rockall, Glasgow-Blatchford